ВЛИЯНИЕ «ЗЕЛЕНОЙ ЭКОНОМИКИ» НА ЭКОНОМИЧЕСКОЕ РАЗВИТИЕ И ЭКОЛОГИЧЕСКУЮ БЕЗОПАСНОСТЬ КАЗАХСТАНА (International Journal of Innovative Technologies in Economy, 2019)
Kazakhstan has a huge potential for the use of renewable energy sources, while being the state with the highest rates of greenhouse gas emissions in Central Asia. Despite significant economic, social and environmental benefits, the share of renewable energy in Kazakhstan's electricity production remains low, at 1.1% in 2017. The government intends to increase this figure to 50% by 2050. While Kazakhstan is experiencing some difficulties in diversifying its economy and energy resources, the inclusive concept of green growth is particularly important for the country.The adopted Strategy Kazakhstan 2050: A New Political Course of the Established State «Strategy - 2050» sets clear guidelines for building a sustainable and efficient economic model based on the country’s transition to a green development path.The article analyzes the current status of the transition to «green economy» including the development of renewable energy, green building, environmentally friendly transport, waste management, sustainable and efficient organic agriculture, and rational use of water resources. The scientific article focuses on the key risks, problems and obstacles to the development of the «green economy» in Kazakhstan, as well as offers recommendations and measures to solve existing problems. In addition, the article examines the methods of the government's transition to a «green economy», within which the planned tasks of a large-scale transition to a «green economy» are to be fulfilled.The article can be useful for those who are interested in sustainable economic growth: the government, energy companies, investors in the field of renewable energy and society as a whole.